Transmigration of impacted mandibular canines - case report - Mioara Decusară; Cerasella Dorina Şincar; Gabriela Popa; Gabriel Valeriu Popa (Amaltea Medical Publishing House, 2019)
Transmigration is a rare dental anomaly, characterized by the presence of the mandibular canine impacted who crosses the midline without signs or subjective manifestations. The formation of the impacted cuspid tooth takes place is in normal parameters, but at a given time, without a specific causal factor, the direction of the impacted canine is deviated towards the median and mandibular symphysis line, horizontally. Orthodontic treatment of mandibular canine transmigration is determined by radiographic examination, which specifies the intraosseous position of the tooth, the direction of migration, and the quality of the mandibular bone. In this article is presented the case of a 10-year-old girl with mixed dentition, 33 impacted, but palpable buccally, located at the apex of the mandibular incisors, with sagittally-elongated symphysis chin, anterior reverse occlusion and inclination of the vestibule of the lower incisors. On the orthopantomogram, the horizontally impacted mandibular canine was identified, the crown exceeding the median line at the apex of the mandibular incisors. Surgical orthodontic treatment aimed at the alignment of the arches and the alignment of the included mandibular canine, obtaining the correspondence of the median and inter-incisal lines and correcting the frontal inverse occlusion.